Evaluation of drug susceptibility profile of mycobacterium tuberculosis lineage 1 from brazil based on whole genome sequencing and phenotypic methods - Guimarães, Arthur Emil dos Santos (2020)
BACKGROUND The evaluation of procedures for drug susceptibility prediction of Mycobacterium tuberculosis based on genomic data against the conventional reference method test based on culture is realistic considering the scenario of growing number of tools proposals based on whole-genome sequences (WGS). OBJECTIVES This study aimed to evaluate drug susceptibility testing (DST) outcome based on WGS tools and the phenotypic methods performed on isolates of M. tuberculosis Lineage 1 from the state of Pará, Brazil, generally associated with low levels of drug resistance. METHODOLOGY Culture based DST was performed using the Proportion Method in Löwenstein-Jensen medium on 71 isolates that had been submitted to WGS. We analysed the seven main genome sequence-based tools for resistance and lineage prediction applied to M. tuberculosis and for comparison evaluation we have used the Kappa concordance test. FINDINGS When comparing the WGS-based tools against the DST, we observed the highest level of agreement using TBprofiler. Among the tools, TB-profiler, KvarQ and Mykrobe were those which identified the largest number of TB-MDR cases. Comparing the four most sensitive tools regarding resistance prediction, agreement was observed for 43 genomes. MAIN CONCLUSIONS Drug resistance profiling using next-generation sequencing offers rapid assessment of resistanceassociated mutations, therefore facilitating rapid access to effective treatment.